O ethos cultural amazônico em Dalcídio Jurandir: aportes para uma teologia amazônica - Silva, Antonio Carlos Teles da (2010)
This work of research has the purpose of developing a theological reflection about cabocla Amazonian culture from de work of a marajoara writer Dalcídio Jurandir. We had started from the presupposition that, in spite of the importance that the Amazon region has acquired, the knowledge about the region (still) remains limited because of the labels that were attributed to it throughout its occupation. We had understood that the process is a historic cultural invisibility, that in its usage, it is translated as a socio-politic invisibility. In this way, this elaboration is specifically in the riverain cabocla culture of the region of the Marajó Islands. The examination of this culture, inside of the intuitions of the Latin American Theology, is a contribution to the fights in defense of the region, of its peoples and its cultural ethos. At the beginning the life and work of Dalcídio Jurandir are situated in his moment: the first half of the XX century, the moment in which it has consolidated, in Amazon, the capitalist exploration system, with the consequent erosion of cultural ethos of the acculturated Brazilian Indian Caboclo. The perspective of the research is definite by the reflection between two distinct visions about the region: the one about the writer Euclides da Cunha and the one of the native of Pará poet, João de Jesus Paes Loureiro. As a theoretical base, it was done an analysis about the constructed representations around Amazon concerning as to the situation of the region in the latest four decades as searching to the contemporary reflection about the relation between representation and identities. The hermeneutic framework makes use of the main themes of the contemporary theology Latin-American, especially the ethics from the victims having like a base, the work of Enri que Dussel. It is also emphasized the relationship between theology and cultural from the Theology of the Culture of Paul Tillich. The reflection properly theological, is developed inside of four themes, related to the Amazon cultural: a reading of Marajó from its opposites, a cabocla identity Theology, the Amazon ecofeminism as a resistence and a Theology of the Amazon Waters.